European policies and legislation targeting ocean acidification in european waters - Current state. (August 2020) - Galdies, Charles; Bellerby, Richard; Canu, Donata; Chen, Wenting; Garcia-Luque, Enrique; Gašparović, Blaženka; Godrijan, Jelena; Lawlor, Paul J.; Maes, Frank; Malej, Alenka; Panagiotaras, Dionisios; Romera, Beatriz Martinez; et al.
Abstract: Ocean acidification (OA) is a global problem with profoundly negative environmental, social and economic consequences. From a governance perspective, there is a need to ensure a coordinated effort to directly address it. This study reviews 90 legislative documents from 17 countries from the European Economic Area (EEA) and the UK that primarily border the sea. The primary finding from this study is that the European national policies and legislation addressing OA is at best uncoordinated. Although OA is acknowledged at the higher levels of governance, its status as an environmental challenge is greatly diluted at the European Union Member State level. As a notable exception within the EEA, Norway seems to have a proactive approach towards legislative frameworks and research aimed towards further understanding OA. On the other hand, there was a complete lack of, or inadequate reporting in the Marine Strategy Framework Directive by the majority of the EU Member States, with the exception of Italy and the Netherlands. We argue that the problems associated with OA and the solutions needed to address it are unique and cannot be bundled together with traditional climate change responses and measures. Therefore, European OA-related policy and legislation must reflect this and tailor their actions to mitigate OA to safeguard marine ecosystems and societies. A stronger and more coordinated approach is needed to build environmental, economic and social resilience of the observed and anticipated changes to the coastal marine systems.